Evaluation of recombinant SEA-TSST fusion toxoid for protection against superantigen induced toxicity in mouse model. (1st September 2015) - Reddy, Prakash Narayana; Paul, Soumya; Sripathy, Murali H.; Batra, Harsh Vardhan
Abstract: Treatment of Staphylococcus aureus infections has become complicated owing to growing antibiotic resistance mechanisms and due to the multitude of virulence factors secreted by this organism. Failures with traditional monovalent vaccines or toxoids have brought a shift towards the use of multivalent formulas and neutralizing antibodies to combat and prevent range of staphylococcal infections. In this study, we evaluated the efficacy of a fusion protein (r-ET) comprising truncated regions of staphylococcal enterotoxin A (SEA) and toxic shock syndrome toxin (TSST-1) in generating neutralizing antibodies against superantigen induced toxicity in murine model. Serum antibodies showed specific reactivity to both SEA and TSST-1 native toxins. Hyperimmune serum from immunized animals protected cultured splenocytes from non-specific superantigen induced proliferation completely. Passive antibody administration prevented tissue damage from acute inflammation associated with superantigen challenge from S. aureus cell free culture supernatants. Approximately 80% and 50% of actively and passively immunized mice respectively were protected from lethal dose against S. aureus toxin challenge. This study revealed that r-ET protein is non-toxic and a strong immunogen which generated neutralizing antibodies and memory immune response against superantigen induced toxic effects in mice model. Highlights: A non-toxic r-ET fusion protein is constructed comprising enterotoxin A and TSST-1. Mouse r-ET antibodies were able to bind to native SEA and TSST-1 toxins. Serum antibodies neutralized the superantigen induced proliferation of lymphocytes. Passive antibody treatment protected mice from toxin induced inflammation of tissues. High percentage of immunized mice were protected from lethal dosage of toxins.